Analysis of the Cerebrospinal Fluid Flow in the Stenosed Aqueduct of Sylvius - H, Edi Azali; A G, Ahmad Lutfi; S, Amir Hamzah; Osman, Kahar; A K, Mohammed Rafiq; Abd. Aziz, Azian; Sa'at@Yusof, Azlin (2011)
Introduction: A 3D model of the aqueduct of Sylvius, i.e. the region of interest (ROI) in the human ventricular system (HVS) is used to investigate the flow of CSF within the human brain, using Computational Fluid Dynamics (CFD). CSF can be modeled as a Newtonian Fluid and its flow through the ROI can be visualized using CFD. In this investigation a 3D geometric model of the ROI is constructed from MRI data. The flow of CSF within the ROI is a complicated phenomenon due to the complex ROI geometry. Different flow rate was simulated at the foramen of Monro and a small stenosis was modeled at the middle of the Aqueduct of Sylvius. Understanding the nature of CSF flow may allow engineers and physicians to design medical techniques and drugs to treat various ventricular complications, such as hydrocephalus as a result of obstruction. Objective: To analyze cerebrospinal fluid flow through the region of interest i.e.Aqueduct of Sylvius. Scopes: •With&withoutblockageinAqueductofSylvius. •Numericalstudy(3D-modelling). •Laminar and turbulence model is used.